Guideline Assessment Project: Filling the GAP in Surgical Guidelines. Issue 4 (April 2019) - Antoniou, Stavros A.; Tsokani, Sofia; Mavridis, Dimitrios; López-Cano, Manuel; Antoniou, George A.; Stefanidis, Dimitrios; Francis, Nader K.; Smart, Neil; Muysoms, Filip E.; Morales-Conde, Salvador; Bonjer, Hendrik Jaap; Brouwers, Melissa C.
Abstract : Objective: The aim of the study was to identify clinical practice guidelines published by surgical scientific organizations, assess their quality, and investigate the association between defined factors and quality. The ultimate objective was to develop a framework to improve the quality of surgical guidelines. Summary Background Data: Evidence on the quality of surgical guidelines is lacking. Methods: We searched MEDLINE for clinical practice guidelines published by surgical scientific organizations with an international scope between 2008 and 2017. We investigated the association between the following factors and guideline quality, as assessed using the AGREE II instrument: number of guidelines published within the study period by a scientific organization, the presence of a guidelines committee, applying the GRADE methodology, consensus project design, and the presence of intersociety collaboration. Results: Ten surgical scientific organizations developed 67 guidelines over the study period. The median overall score using AGREE II tool was 4 out of a maximum of 7, whereas 27 (40%) guidelines were not considered suitable for use. Guidelines produced by a scientific organization with an output of ≥9 guidelines over the study period [odds ratio (OR) 3.79, 95% confidence interval (CI), 1.01–12.66, P = 0.048], the presence of a guidelines committee (OR 4.15, 95% CI, 1.47–11.77, P = 0.007), and applying the GRADE methodology (OR 8.17, 95% CI, 2.54–26.29, P < 0.0001) were associated with higher odds of being recommended for use. Conclusions: Development by a guidelines committee, routine guideline output, and adhering to the GRADE methodology were found to be associated with higher guideline quality in the field of surgery. Abstract : Supplemental Digital Content is available in the text